Social effect of implementing wellness programs during pregnancy (Research Announcements "Heritage BG", 2025)
Pregnancy is the most important period for the formation of future life. The fetal stage is crucial not only for the physical development of a human being, but simultaneously it initiates the shaping of non-tangible characteristics. Wellness programs for pregnant women contribute to effective health promotion and preventive care, which in turn results in significant social long-term benefits. Effective wellness programs facilitates the birth of healthy children. Building a strong foundation of wellness culture among mothers allows for the implementation of a healthy lifestyle filled with a multiplicity of social effects through the upbringing of healthy offspring. References:Dimitrova 2019: Dimitrova, Bistra. Quality Assessment about Standards for Wellness Services and Certified Skills of Specialized Staff. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, 17 (2): 143-149. ISSN: 1313-3551 (online) / http://tru.uni-sz.bg/tsj/Vol.17Tomova 2021: Tomova, Tatiana. Menstrualni raztroistva –razpostranenie i proyava. International Scientific journal Smart Innovations in Recreational, Wellness Industry and Niche Tourism. 3(2), 33-38. ISSN 2603 493X (online). Available at: https://scjournalbg.globalwaterhealth.org// (11.03.2023)Clatworthy 2012: Clatworthy, John. The Effectiveness of Antenatal Interventions to Prevent Postnatal Depression in High-risk Women. J Affect Disord 137: 25-34.Dimitrova 2019: Dimitrova, Bistra. Quality Assessment about Standards for Wellness Services and Certified Skills of Specialized Staff. DOI: 10.15547 / tjs.2019.02.007. Trakia Journal of Sciences, 17 (2): 143-149. ISSN: 1313-3551 (online) / http://tru.uni-sz.bg/tsj/Vol.17Donev et al. 2019: Donev Jordan, Stoyan Andonov, Stefka Djobova, Jordan Jordanov, Oleg Hristov, Ivelina Kirilova, Stoyan Bahchevanski, Rumen Iossifov, Velichka Aleksandrova, Bogomil Angelov, Natalia Stoyanova. Comparative study of measuring physical activity among sport students. Original scientific paper. Conference: International scientific congress ‘Applied sports sciences. Balkan scientific congress of physical education, sports and health’, 15 – 16 November 2019: 369-374, Sofia, Bulgaria. Proceedings book, NSA press, Sofia. ISBN (Print): 978-954 718-602-6.Dumas et al. 2009: Dumas G.A., Leger A., Plamondon A., Charpentier K.M., Pinti A., Mcgrath M. Fatigability of Back Extensor Muscles and Low Back Pain During Pegnancy. Clin Biomech (Bristol, Avon). 2010 Jan;25(1):1-5. Available at: do10.1016/j.clinbiomech.2009.09.011// (19.01. 2023).Dunkel Schetter, Tanner 2012: Dunkel Schetter, Christine; Lynlee Tanner. Anxiety, Depression and Stress in Pregnancy: Implications for Mothers, Children, Research, and Practice. Curr Opin Psychiatr 25:141-148. Available at: doi: 10.1097/YCO.0b013e3283503680// (19.01.2023)Glover 2014: Glover, Vivette. Maternal Depression, Anxiety and Stress During Pregnancy and Child Outcome: What Needs to be Done. Best Pract Res Clin Obstet Gynaecol 28: 25-35. Available at: doi: 10.1016/j.bpobgyn.2013.08.017// (20.01.2023)Goodman, Santangelo 2011: Goodman, Janice, Gabrielle Santangelo. Group Treatment for Postpartum Depression: A Systematic Review. Arch Womens Ment Health 14: 277-293. Available at: DOI: 10.1007/s00737-011-0225-3// (20.02.2023).Ilinоva, Tоteva 2019: Ilinova, Bogdana, Maria Toteva. Pregnancy and Delivery оf Elite Cоmpetitive Athletes. Internatiоnal Scientific Cоngress-Applied Spоrts Sciences, Proceeding Bооk, 280-285, NSA 2019. eISBN: 978-954 718-601-9. (Available at: www.icass2019// (20.11.2022).Letourneau et al. 2012: Letourneau, Nicole Lyn, Cindy-Lee Dennis, Karen Benzies, Linda Duffett-Leger, Miriam Stewart, Panagiota D. Tryphonopoulos. Postpartum Depression is a Family Affair: Addressing the Impact on Mothers, Fathers, and Children. Issues Mental Health Nurs 33: 445-457. Available at: doi: 10.3109/ 01612840. 2012. 673054// (20.02.2023).Nesheva 2019: Nesheva, Irina. Study of Results between Initial and Final Specific Tests in Women with Normal Pregnancy. Trakia Journal of Sciences, Sofia, 17 (2): 135-142. Available at: http://tru.uni-sz.bg/tsj/Vol.17,%20Suppl.2,%20,2019/6.pdf // (01.03.2023).Nesheva 2020: Nesheva, Irina. Information System for Inclusion of Women with Normal Pregnancy in Gymnastics Program. ‘Smart Innovations on the Recreative & Wellness Industries and Niche tourism’, Sofia, 2 (1): 33-39. eISSN: 2603-4921. Available at: https://scjournal.globalwaterhealth.org// (01.03.2023).Tsanov, 2015: Tsanov, Ivan. Ikonomika na sporta. Monografiya. Sofiya, BAK.Veselinov, 2021: Veselinov, Dimitar. Dialogat v obrazovaniet. Deseti mezhdunaroden esenen nauchno-obrazovatelen forum Dialogat v obrazovanieto – suvremennost i perspektivi. Sofiya ISBN 978-954-07-5231-0.WHO 2022: World Health Organization. Biology. Science for Ninth Class – Part III – Biology. https://www.who.int/data/gho/data/major-themes/health-and-well-being (13.03.2023).
Keywords: women with normal pregnancy; recreational physical activities; healthy lifestyle; the effect of Wellness programs